The Influence of Practical Drawing Courses on Student Work Competence in SKKNI Building Drawing: Case Study at Surabaya State University - Soeparno, Soeparno; Suparji, Suparji; Wiyono, Agus; Hidayati, Lutfiyah; Baskoro, Farid (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the influence of emphasizing practical drawing learning methods and work competencies in the SKKNI for building drawings. The majority of respondents work in the vocational school sector with a percentage of 53%. Furthermore, as many as 41% of respondents work in the PT sector. Meanwhile, only 6% of respondents work in the high school sector. The results of the analysis show that the majority of respondents consider these two methods to have a significant impact. The emphasis on